2021
DOI: 10.1016/j.jbc.2021.100285
|View full text |Cite
|
Sign up to set email alerts
|

Decreases in different Dnmt3b activities drive distinct development of hematologic malignancies in mice

Abstract: DNA methylation regulates gene transcription and is involved in various physiological processes in mammals, including development and hematopoiesis. It is catalyzed by DNA methyltransferases including Dnmt1, Dnmt3a, and Dnmt3b. For Dnmt3b, its effects on transcription can result from its own DNA methylase activity, the recruitment of other Dnmts to mediate methylation, or transcription repression in a methylation-independent manner. Low-frequency mutations in human DNMT3B are found in hematologic malignancies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 63 publications
(96 reference statements)
1
11
0
Order By: Relevance
“…In Myc-induced lymphoma, expedited lymphomagenesis is associated with increased expression of a truncated catalytically-inactive dominant-negative isoform, DNMT3B7 ( 196 ). This observation is corroborated by a recent study that showed that mice expressing a catalytically-inactive DNMT3B isoform from one or both alleles develop B-cell lymphomas among other hematologic malignancies ( 197 ). In non-small cell lung cancer (NSCLC), the ΔDNMT3B subfamily was described, consisting of at least seven DNMT3B variants resulting from alternative splicing, some lacking enzymatic activity ( 198 ).…”
Section: Mechanisms Controlling Dnmt Expression In Cancersupporting
confidence: 63%
“…In Myc-induced lymphoma, expedited lymphomagenesis is associated with increased expression of a truncated catalytically-inactive dominant-negative isoform, DNMT3B7 ( 196 ). This observation is corroborated by a recent study that showed that mice expressing a catalytically-inactive DNMT3B isoform from one or both alleles develop B-cell lymphomas among other hematologic malignancies ( 197 ). In non-small cell lung cancer (NSCLC), the ΔDNMT3B subfamily was described, consisting of at least seven DNMT3B variants resulting from alternative splicing, some lacking enzymatic activity ( 198 ).…”
Section: Mechanisms Controlling Dnmt Expression In Cancersupporting
confidence: 63%
“…Moreover, both in AML and DLBCL, high DNMT3B levels are correlated with a bad prognosis and a more aggressive disease (141,142). However, while most studies indicate that DNMT3B has oncogenic properties in hematological cancers, some studies have also reported the opposite (143)(144)(145). For example, Dnmt3b deletion in the MLL-AF9 driven AML mouse model led to accelerated progression (146).…”
Section: • Dnmt3bmentioning
confidence: 99%
“…For example, Dnmt3b deletion in the MLL-AF9 driven AML mouse model led to accelerated progression (146). Furthermore, Dnmt3b haploinsufficiency in mice resulted in the development of various hematologic malignancies, including TCL (145). In MM, Amodio et al reported an inverse correlation between miR-29b and DNMT3B levels and showed that targeting DNMT3A/B using miR-29b mimics reduces MM cell growth, indicating that DNMT3A/B has an oncogenic role in MM (138).…”
Section: • Dnmt3bmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, mutations in DNMT3B have been found in several hematological malignancies including cutaneous T-cell lymphomas and B-cell lymphomas [80]. Moreover, Dnmt3b-deficient mice display genome-wide hypomethylation, increased expression of several oncogenes, and develop T-cell lymphomas and chronic lymphocytic leukemia [81]. TET1 was identified as a fusion partner of the mixed-lineage leukemia (MLL) gene from the breakpoint of chromosomal translocation in acute myeloid leukemia (AML) [82], and loss of TET2 is strongly associated with myelodysplastic syndromes, myeloproliferative neoplasms, and myeloid leukemias [83].…”
Section: Is There a Link Between Active Demethylation And Malignant Transformation?mentioning
confidence: 99%